Catalytic Conversion of Carbon Dioxide to Methanol: Current Status and Future Perspective - Zhang, Xinbao; Zhang, Guanghui; Song, Chunshan; Guo, Xinwen (Frontiers in Energy Research, 2021)
With the increasing environmental problems caused by carbon dioxide (CO2) emission and the ultimate carbon resources needed for the development of human society, CO2 hydrogenation to methanol with H2 produced with renewable energy represents a promising path forward. Comprehensive analysis shows that the production of methanol by thermal catalytic CO2 hydrogenation is the most promising technology for large-scale industrialization. This review highlights current developments and future perspectives in the production of methanol from CO2, as well as the main existing problems based on a thorough techno-economic analysis. Moreover, the utilization status and future role of methanol as a platform molecule in the energy system is analyzed. Finally, in this review attention is paid to the development of new catalysts, new routes and new technologies for CO2 conversion aiming to clarify the future direction.